Using unreal chemist mobile application as potential tool in learning chemistry - Pepino, Chese Ann M. (University of the Philippines Cebu, 2023)
The study utilized a quasi-experimental method of the pretest-posttest design with pre-selected groupings for both experimental groups. The study was conducted at a private school institution located at Talisay, City Cebu. The study used a validated research-constructed questionnaire to determine the performance of the students during the experimentation. A pretest was administered to both groups before the implementation of the proposed intervention. Both experimental groups were exposed to hands-on laboratory experiments and the use of Unreal Chemist Mobile Application. After the implementation of the interventions, a posttest was administered, an attitude survey toward Chemistry was administered to both experimental groups, and another attitude survey towards the proposed intervention was administered to experimental group 2. The findings of the study showed both of the experimental groups had a Below Average performance in the pretest and posttest. That is because of the limited time the students were exposed to the intervention. Both groups had a significant improvement in terms of their performance from the pretest to the posttest. The experimental group 2 was positive about the use of Unreal Chemist mobile application as a potential tool in learning Chemistry. In terms of their perception towards Chemistry, both of the experimental groups agreed on the positive impact of Chemistry.